PENGARUH LATIHAN POWER LENGAN TERHADAP KEMAMPUAN TOLAK PELURU DALAM CABANG OLAGRAGA ATLETIK PADA SISWA SMA NEGERI 3 TONDANO - Lomboan, Ellen B.; Malonda, Jeanne (JURNAL ILMIAH KESEHATAN MANADO, 2024)
The problem in this study is whether there is an effect of arm power training on the ability to repel bullets in athletic sports in students of SMA Negeri 3 Tondano? Research Objective: to find out how much effect arm power training has on the ability to repel bullets in athletic sports in students of SMA Negeri 3 Tondano? Research Hypothesis: There is an Effect of Arm Power Training on the Ability to Repel Bullets in Athletic Sports in SMA Negeri 3 Tondano Students. The research method used is an experimental method with treatment in the form of exercises given for six weeks. The population in this study is all students of SMA Negeri 3 Tondano Putera totaling 79 people and a sample of 20 people, then divided into 2 groups by lottery who get an odd number is the experimental group and the one who gets an even number is the control group. Data collection instrument: Bullet repulsion test. The research design used: randomized control groups pre-test and post-test design. The hypothesis test uses statistical techniques with the t-test. The results of the hypothesis analysis obtained an observation t of 25.36 while the table t obtained from the degree of freedom n-1 + n2 – 2 is 10 + 10 – 2 = 18 and the level of confidence = 0.05 is 2.101. According to the test criteria, accept Ho if t observation is smaller than t table and reject Ho if t observation is greater than t table. Because t observations are greater than t tables, the results of the analysis show rejection of Ho and acceptance of Ha. Research conclusion: There is an effect of arm power training on the ability to repel bullets in athletic sports in students of SMA Negeri 3 Tondano.